Analysis of study plans and the professional exercise of industrial engineering in the countries of the Pacific Alliance - Gonzáles Araujo, Luis Alberto (2022)
This document is the product of collaborative work in REDIN, the network of industrial engineering programs in the central Colombian node of ACOFI, and the result of a research project articulated with the National Professional Engineering Council to review the programs and the professional practice of industrial engineers in the countries belonging to the Pacific Alliance (PA). This document analyzes the essential elements for articulating the Industrial Engineering programs and the professional practice of the industrial engineer in the different countries of the PA. This study proposes guidelines to highlight the importance and need of the professional license as a fundamental axis for professional practice at an international level and to articulate the different trends in education and research in Industrial Engineering. Finally, the document incorporates actions to promote and develop the study of the necessary aspects to standardize the criteria and parameters for the exercise of Colombian engineering in other international scenarios.